2023
DOI: 10.1186/s12866-023-02849-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated quinolone resistance genes detected in Ciprofloxacin non-susceptible Escherichia coli and Klebsiella isolated from children under five years at hospital discharge, Kenya

Abstract: Background The increasing spread of fluoroquinolone resistant enteric bacteria is a global public health concern. Children recently discharged from the hospital are at high risk of carriage of antimicrobial resistance (AMR) due to frequent exposure to antimicrobials during inpatient stays. This study aimed to determine the prevalence, correlates of ciprofloxacin (CIP) non-susceptibility, and distribution of plasmid-mediated quinolone resistance (PMQR) genes in Escherichia coli (E. coli) and Kle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…Consistent with our findings, a study at a tertiary hospital in southern Nigeria revealed that 93.3% of E. coli isolates harboured at least one fluoroquinolone resistance gene [27]. Similar patterns of high levels of fluoroquinolone re-sistance have been reported in other parts of sub-Saharan Africa including South Africa and Kenya [10,[28][29][30][31]. In our study, fluoroquinolone resistance in E.coli and P. aeruginosa was primarily conferred by double or triple mutations in the gyrA gene.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings, a study at a tertiary hospital in southern Nigeria revealed that 93.3% of E. coli isolates harboured at least one fluoroquinolone resistance gene [27]. Similar patterns of high levels of fluoroquinolone re-sistance have been reported in other parts of sub-Saharan Africa including South Africa and Kenya [10,[28][29][30][31]. In our study, fluoroquinolone resistance in E.coli and P. aeruginosa was primarily conferred by double or triple mutations in the gyrA gene.…”
Section: Discussionsupporting
confidence: 91%
“…Antibiotics are an essential, and often life-saving tool for hospitalized children in settings of high infectious-disease related morbidity and mortality. Phenotypic AMR was associated with longer period of hospitalization and antibiotic use during hospitalization consistent with our previous findings [ 17 , 18 ] and findings from studies conducted elsewhere [ 19 ]. We observed a high prevalence of non-susceptibility to 3 rd generation cephalosporins (cefotaxime, ceftriaxone and ceftazidime) in our study sites, as has been described elsewhere in SSA [ 20 – 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Polymerase chain reaction (PCR) was used to detect the respective ARGs (Table S1 ) of chloramphenicol, macrolides, quinolones, β-lactams, tetracyclines, and aminoglycosides, which are widely used in animals. gyr A and par C targets in the quinolone resistance determining region (QRDR) of 7 strains with different PFGE types and high fluoroquinolone resistance [ 27 ] (MIC ≥ 32 mg/L) were detected. The gyrA and parC sequences were compared with those of E. coli K12 available in the NCBI database.…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization (WHO) has classified fluoroquinolones as “critically important antimicrobials” because of their broad-spectrum effects and clinical importance in human and animal medicine [ 25 ]. Some studies have shown that minimal inhibitory concentration (MIC) ≥ 32 mg/L is a high-level resistant strain [ 26 , 27 ]. In this study, an MDR E. coli C3 highly resistant to multiple antibiotics was isolated from E. coli isolated from different animals in northeast China.…”
Section: Introductionmentioning
confidence: 99%